Statistical Model-Based Classification to Detect Patient-Specific Spike-and-Wave in EEG Signals - Quintero-Rincón, Antonio (2020)
Fil: Quintero-Rincón, Antonio. Pontificia Universidad Católica Argentina; Argentina